(untitled) (Scientific Annals of Economics and Business, 2022)
The present research aims to establish the antecedents of sustainable entrepreneurial intention, having as reference theoretical framework the model of entrepreneurial event and the model of planned behavior, integrated and adapted to the context of sustainable entrepreneurship. At the level of investigated population, consisting of 150 students from two Serbian universities, the empirical results emphasized that: personality traits and environmental values are significant and direct predictors of behavioral characteristics; entrepreneurial education and behavioral characteristics have an indirect influence on sustainable entrepreneurial intention being mediated by the desire and feasibility of sustainable entrepreneurship perceived by respondents. As theoretical utility of the research, the current study is among the few that tried to integrate and expand two competing models in order to establish the antecedents of sustainable entrepreneurial intent. The research model adopted variables specific for the two models and integrated personality traits, environmental values and entrepreneurial education in order to establish direct and indirect determinants of sustainable entrepreneurial intention. At practical level, the validation of the research model emphasizes the utility of stimulating youth’ sustainable entrepreneurial intention and applicability for future academic research endeavors. In order to stimulate sustainable entrepreneurial intentions, the validated research model indicates to governmental and university decision makers the need to implement programs promoting environmental values and integrating sustainability into the entrepreneurial education of youth.